Molecular dynamics perspective of the effects of laser thermal configurations on the dislocation and mechanical characteristics of FeNiCrCoCu HEA through powder bed fusion process. (December 2022) - Jamil, Ishat Raihan; Mustaquim, Ali Muhit; Islam, Mahmudul; Hasan, Mohammad Nasim
Abstract: The implication of process thermal conditions on the dislocation and mechanical characteristics of FeNiCrCoCu high entropy alloy (HEA) blocks manufactured through powder bed fusion (PBF) under various laser configurations were explored using molecular dynamic (MD) study. The PBF process parameters have been systematically altered, such as laser scan speed from 0.4 Å/ps to 0.1 Å/ps, 1–4 unidirectional and reversing laser passes, as well as laser power from 100 µW to 220 µW, following previous literature. The results suggest that reducing the laser scanning speed up to a critical velocity of 0.2 Å/ps considerably improves mechanical strengths, however further speed reduction creates severe surface defects. Alternatively, the material's strengths could be effectively improved by annealing with multiple unidirectional laser passes over the same target area, rather than reversing the direction after subsequent passes. Interestingly, increasing laser power aids in the amelioration of material density ultimately leading to higher ultimate tensile strength (UTS) even in non-dislocation free structures. Dislocation analysis reveals that for single laser pass situations, the annihilation of the bulk sessile dislocations during tensile straining marks an early yield failure, leading to decreased UTS. Whereas, the yield points are more subtle in annealed blocks, allowing them to achieve higher UTS. Likewise, fewer sessile dislocations and stacking faults correspond to better ultimate compressive strength (UCS), although the compressive yield points are usually indistinguishable in most instances. Present atomistic findings enable researchers in understanding the underlying effects and help in the process optimization of emerging microscale additive manufacturing processes. Graphical Abstract: ga1